Spinal cord injury induces widespread chronic changes in cerebral white matter. Issue 7 (21st April 2017) - Ilvesmäki, Tero; Koskinen, Eerika; Brander, Antti; Luoto, Teemu; Öhman, Juha; Eskola, Hannu
Abstract: Traumatic spinal cord injuries (SCIs) lead to axonal damage at the trauma site, as well as disconnections within the central nervous system. While the exact mechanisms of the long‐term pathophysiological consequences of SCIs are not fully understood, it is known that neuronal damage and degeneration are not limited to the direct proximity of the trauma. Instead, the effects can be detected even in the cerebrum. We examined SCI‐induced chronic brain changes with a case‐control design using 32 patients and 70 control subjects. Whole‐brain white matter (WM) tracts were assessed with diffusion tensor imaging (DTI). In addition, we analysed associations between DTI metrics and several clinical SCI variables. Whole‐brain analyses were executed by tract‐based spatial statistics (TBSS), with an additional complementary atlas‐based analysis (ABA). We observed widespread, statistically significant ( P ≤ 0.01) changes similar to neural degeneration in SCI patients, both in the corticospinal tract (CST) and beyond. In addition, associations between DTI metrics and time since injury were found with TBSS and ABA, implying possible long‐term post‐injury neural regeneration. Using the ABA approach, we observed a correlation between SCI severity and DTI metrics, indicating a decrease in WM integrity along with patient sensory or motor scores. Our results suggest a widespread neurodegenerative effect of SCI within the cerebrum that is not limited to the motor pathways. Furthermore, DTI‐measured WM integrity of chronic SCI patients seemed to improve as time elapsed since injury. Hum Brain Mapp 38:3637–3647, 2017 . ©2017 Wiley Periodicals, Inc.